2019
DOI: 10.3390/electronics8121559
|View full text |Cite
|
Sign up to set email alerts
|

An Image Compression Method for Video Surveillance System in Underground Mines Based on Residual Networks and Discrete Wavelet Transform

Abstract: Video surveillance systems play an important role in underground mines. Providing clear surveillance images is the fundamental basis for safe mining and disaster alarming. It is of significance to investigate image compression methods since the underground wireless channels only allow low transmission bandwidth. In this paper, we propose a new image compression method based on residual networks and discrete wavelet transform (DWT) to solve the image compression problem. The residual networks are used to compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…) to analyze and denoise measured data in a variety of applications and services (e.g., wind speed prediction, air quality prediction, underground mine applications, neural audio caption, etc.). Several practical experiments were given in these articles, and the results indicated that the performance of the improved deep learning methods could be higher than the performance of conventional machine learning methods [43][44][45][46][47][48][49][50][51][52][53][54][55][56].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…) to analyze and denoise measured data in a variety of applications and services (e.g., wind speed prediction, air quality prediction, underground mine applications, neural audio caption, etc.). Several practical experiments were given in these articles, and the results indicated that the performance of the improved deep learning methods could be higher than the performance of conventional machine learning methods [43][44][45][46][47][48][49][50][51][52][53][54][55][56].…”
Section: Discussionmentioning
confidence: 99%
“…In the experiments, this study collected the images from the COCO 2014 dataset and the images of underground mines for training and testing. The results show that the peak signal-to-noise ratio (PSNR) and the structural similarity (SSIM) of the proposed method were higher than the PSNR and the SSIM of other methods (e.g., denoising-based approximate message passing (D-AMP), ReconNet and total variation augmented Lagrangian alternating direction algorithm (TVAL3)) [46].…”
Section: Wan Et Al From China In "Multivariate Temporal Convolutionamentioning
confidence: 92%
See 1 more Smart Citation
“…In [ 13 ], the concept of ‘Wavelet-based compression of images’ was used in grayscale images with various techniques, such as SPIHT, EZW, and SOFM. In [ 14 ], the authors deal with a specific type of compression by utilizing wavelet transforms. Wavelets were employed as simple patterns/coefficients, reproducing the initial pattern when multiplied and combined.…”
Section: Literature Reviewmentioning
confidence: 99%
“…e feature extraction network is a fully convolutional network. It is mainly composed of 3 × 3 and 1 × 1 convolution kernels and a large number of shortcut links with residual units [35][36][37]. e structure of the feature extraction network is shown in Figure 2.…”
Section: Architecture Of the Object-text Detection Networkmentioning
confidence: 99%